Explain the Components of Urban Branding, Emphasizing the Dimensions of Tourism - Maryam Vahabian; Nowzar Ghanbari; Said Ali Nori; Bizhan Kalhornia (Shock and Vibration)
Currently, change in cities is advancing due to technological advances, information floods, increasing awareness, and raising living standards. Although the development of a city depends on the activation of urban marketing, an important and well-known city stands out as a brand. One of the strategies of urban management in order to progress in the competitive world market is to plan for sustainable urban branding for the city, which introducing the capabilities of the city, the most important factors in achieving economic benefits of urban branding are tourism and physical space. The metropolis of Hamadan has been selected for this purpose, including urban tourism destinations with historical and touristic species and the capital of Iran’s history and civilization. The measurement tool in this study is a questionnaire that will be designed based on the conceptual framework of the research as well as related studies. For this purpose, the components and indicators of urban branding have been identified with emphasis on social, economic, cultural, and physical dimensions and have been used with the opinion of 30 urban experts and specialists and using SPSS25 software analysis at a significant level. It can be concluded that according to the respondents, these variables have a great impact on branding the metropolis of Hamadan.